2020
DOI: 10.1002/hep.31304
|View full text |Cite
|
Sign up to set email alerts
|

C24‐Ceramide Drives Gallbladder Cancer Progression Through Directly Targeting Phosphatidylinositol 5‐Phosphate 4‐Kinase Type‐2 Gamma to Facilitate Mammalian Target of Rapamycin Signaling Activation

Abstract: Background and Aims The wide prevalence of chemoresistance and compromised early diagnosis of gallbladder cancer (GBC) has led to poor patient prognosis, requiring sustained efforts for the identification of effective biomarkers and therapeutic intervention. Ceramides have emerged as intracellular signaling molecules linked to tumorigenesis and therapeutic response in cancers. However, the clinical relevance of ceramides with GBC has not been investigated. Approach and Results In the present study, we revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…26 Indeed, extensive studies have uncovered specific biological roles of ceramide species including C 16 -ceramide, 27,44-47 C 18 -ceramide, 48 and C 24ceramide. 9 Therefore, this study discloses a function for C 24:1 ceramide that is quite distinct from that of C 16 -ceramide, consistent with the many ceramides hypothesis.…”
Section: F I G U R Esupporting
confidence: 85%
See 2 more Smart Citations
“…26 Indeed, extensive studies have uncovered specific biological roles of ceramide species including C 16 -ceramide, 27,44-47 C 18 -ceramide, 48 and C 24ceramide. 9 Therefore, this study discloses a function for C 24:1 ceramide that is quite distinct from that of C 16 -ceramide, consistent with the many ceramides hypothesis.…”
Section: F I G U R Esupporting
confidence: 85%
“…Recently, some studies have proposed specific roles for distinct ceramide species in cell pathobiology. 9,26,27 We investigated the roles of ceramide species in the formation of lamellipodia. In CerSs-knocked down cells, the cellular sphingolipid profile for ceramides, and their derivatives such as sphingomyelins and hexosylceramides were determined.…”
Section: Roles Of Ceramide Species In the Formation Of Lamellipodiamentioning
confidence: 99%
See 1 more Smart Citation
“…First, the enhanced synthesis of Cer, in addition to S1P and glucosylceramide, is a tool employed by cancer cells to increase survival [ 46 ]. Short chain Cers such as C2 Cer and C6 Cer have been demonstrated to be involved in the modulation of immunocytes and in the proinflammatory responses [ 54 , 55 ]. Moreover, in inflammatory diseases, sphingolipids are able to act as anti- or pro-inflammatory mediators and participate in controlling leukocyte activation and migration.…”
Section: Targeting S1p Signalling To Improve Immunotherapymentioning
confidence: 99%
“…In particular, many inflammatory processes and pathologies, including cardiovascular diseases, neurodegenerative disorders, lung inflammatory disorders (such as chronic obstructive pulmonary disease (COPD) or asthma) type 2 diabetes or cancer, are characterized by disruption of sphingolipid homeostasis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Moreover, it has been reported that treatment with short-chain Cer anologs is an effective treatment against certain cancers [ 22 , 23 , 24 ]. In addition, deoxy-sphingolipids have been shown to be of great importance when observing their potential as regulators of sphingolipid metabolism.…”
Section: Introductionmentioning
confidence: 99%